Use Of The Works Of Eastern Thinkers In Preparation Of Future Primary School Teachers For Professional Activity - X.A. Turakulov; S. Saidaxmatov (International Scientific and Current Research Conferences, 2020)
The current global changes in the socio-economic and scientific-technical spheres require the improvement of the system of training, in particular, the system of future specialists on the basis of innovative and integrative education. This means paying special attention to the definition of pedagogical and psychological bases of teaching on the basis of innovative-integrative education, the development of creative and professional approaches of students to secondary education in the educational process